2018
DOI: 10.3389/fnagi.2018.00345
|View full text |Cite
|
Sign up to set email alerts
|

In Older Patients Treated for Dizziness and Vertigo in Multimodal Rehabilitation Somatic Deficits Prevail While Anxiety Plays a Minor Role Compared to Young and Middle Aged Patients

Abstract: Objective: Many patients with dizziness and vertigo are of older age. It is still unclear which age-associated factors play a role in the treatment of dizziness and vertigo. Therefore, age-associated characteristics of patients subjected to an interdisciplinary day care approach for chronic vertigo and dizziness were analyzed.Subjects and Methods: 650 patients with chronic dizziness/vertigo subjected to a multimodal vestibular rehabilitation day care program were analyzed. Information concerning age, gender, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The data were prospectively collected between June 2013 and March 2017 in the Center for Vertigo and Dizziness of Jena University Hospital. These data have already been analyzed to define age‐related characteristics of patients with chronic dizziness (Dietzek et al., 2018). The study was approved by the local ethics committee (ethics committee of the Friedrich‐Schiller‐University Jena, number 5426‐02/18).…”
Section: Methodsmentioning
confidence: 99%
“…The data were prospectively collected between June 2013 and March 2017 in the Center for Vertigo and Dizziness of Jena University Hospital. These data have already been analyzed to define age‐related characteristics of patients with chronic dizziness (Dietzek et al., 2018). The study was approved by the local ethics committee (ethics committee of the Friedrich‐Schiller‐University Jena, number 5426‐02/18).…”
Section: Methodsmentioning
confidence: 99%
“…Our data also demonstrated an age-dependent decrease in the portion of psychological diagnoses in the adult patients, though the differences were not statistically significant. Dietzek et al 25 reported elderly patients suffering from dizziness scored significantly lower in HADS than the younger patients; moreover, the elderly improved 6 months after therapy especially in Mobility Inventory when alone and in Vertigo Severity Scale (vestibular-balance subscale). However, in our study, the elderly did not show greater improvement in DHI than other age groups.…”
Section: Discussionmentioning
confidence: 98%
“…Many agents might contribute to the causes of dizziness than cure it in older adults ( 45 , 47 ). In addition, anxiety and depression may play a minor role in older patients with dizziness/vertigo compared with younger patients ( 22 ). Therefore, healthcare providers may assume that psychological therapy may have less beneficial effects in older than in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 765 patients with chronic dizziness and vertigo attended a daycare multimodal treatment program ( 22 ) between June 2013 and September 2017 in the Center for Vertigo and Dizziness of Jena University Hospital. The Center for Vertigo and Dizziness is a tertiary care outpatient project consisting of neurology, ear, nose, and throat (ENT), and physiotherapy departments.…”
Section: Methodsmentioning
confidence: 99%